Water Use by Chinese Pine Is Less Conservative but More Closely Regulated Than in Mongolian Scots Pine in a Plantation Forest, on Sandy Soil, in a Semi-Arid Climate - Dang, Hongzhong; Zhang, Xueli; Han, Hui; Chen, Shuai; Li, Mingyang (Frontiers in Plant Science, 2021)
The diversity of plant water use patterns among species and ecosystems is a matter of widespread debate. In this study, Chinese pine (Pinus tabuliformis, CP) and Mongolian Scots pine (Pinus sylvestris var. mongolica, MP), which is co-exist in the shelterbelt plantations in the Horqin Sandyland in northern China, were chosen for comparison of water use traits by monitoring xylem sap flow alongside recordings of the associated environmental factors over four growing seasons. Continuous sap flux density measurements were converted into crown projected area transpiration intensity (Tr) and canopy stomatal conductance (Gs). The results indicated that MP showed a higher canopy transpiration intensity than in CP, with Tr daily means ( standard deviation) of 0.84  0.36 and 0.79  0.43 mm∙d-1, respectively (p = 0.07). However, the inter-annual variability of daily Tr in MP was not significant, varying only approximately a 1.1-fold (p = 0.29), while inter-annual variation was significant for CP, with 1.24-fold variation (p < 0.01). In particular, the daily mean Tr value for CP was approximately 1.7-times higher than that of MP under favorable soil moisture conditions, with values for relative extractable soil water within the 0−1.0 m soil layer (REW) being above 0.4. However, as the soil dried out, the value of Tr for CP decreased more sharply, falling to only approximately 0.5-times the value for MP when REW fell to < 0.2. The stronger sensitivity of Tr and/or Gs to REW, together with the more sensitive response of Gs to VPD in CP, confirms that CP exhibits less conservation of soil water utilization but features a stronger ability to regulate water use. Compared with MP, CP can better adapt to the dry conditions associated with climate change.